Preventive Measures of Cyberbullying on Adolescents in Indonesia - Wahanisa, Rofi; Prihastuty, Rahmawati; Dzikirullah H. Noho, Muhammad (Lentera Hukum, 2021)
The increasing internet penetration in Indonesia has provided adolescents to expose pornographic content advertently. It inevitably includes other adverse impacts like fraud and violence, which begin with cyberspace. Also, cyberbullies on the internet have become a serious concern on how the government has anticipated it to prevent more practices in this cross-border experience. This study aimed to address the causes and impacts of online-based media on adolescents with the following preventive measures to reduce increasing cases of cyberbullying in Indonesia. This study used legal research in assessing the issue by sourcing primary data from statutory regulations and secondary data from academic resources. This study showed that cyberbullying continues to become an annoying issue among children, adolescents, and adults. The existing regulations provide insufficient protection preventing these practices because it does not specifically regulate its types and forms at defining cyberbullying. It suggested introducing a more specific regulation that outlines cyberbullying in ensuring the protection amidst the more borderless communication to prevent more adverse impacts on victims. KEYWORDS: Cyberbullying, Information and Technology Law, Child Protection.